The Correlations Between Disease Specific Quality of Life, Short Form-36 and Clinical Variables in Patients With Ankylosing Spondylitis - Hakan ALKAN; Necmettin YILDIZ; Füsun ARDIÇ (Archives of Rheumatology, 2020)
Objectives: This study aims to assess the correlations between disease specific quality of life (QoL), general health status and clinical variables in patients with ankylosing spondylitis (AS), and also to determine a cutoff value for the disease specific QoL questionnaire. Patients and methods: A total of 124 patients (80 males, 44 females; mean age 40.6±11.1 years; range, 20 to 65 years) who fulfilled the modified New York criteria for AS were included in this cross-sectional study. All patients received a comprehensive rheumatologic assessment including disease specific instruments for disease activity, functional status, spinal mobility and QoL. Furthermore, short form-36 (SF-36) was used to determine general health status. Pain levels of the patients were assessed with visual analog scale (VAS). Pearson’s analysis was used to assess correlation among variables, with moderate, strong, or very strong correlations if the value was between 0.40-0.69, 0.70-0.89, and 0.90-0.99, respectively. To determine a cutoff value for the ankylosing spondylitis quality of life (ASQoL) score, the area under the receiver operating characteristic curve (AUC) was computed according to clinical parameters which have the strongest correlations with ASQoL. Results: The mean ASQoL score was 8.8±4.9. There was a significantly positive correlation between ASQoL and disease activity, functional status, spinal mobility and pain VAS whereas there was a significantly negative correlation between ASQoL and the SF-36 subscale scores except for mental health and emotional role (p<0.001). The strongest positive correlation was found between ASQoL and the Bath Ankylosing Spondylitis Disease Activity Index (r=0.721, p<0.001) whereas the strongest negative correlation was found between ASQoL and the first question of SF-36 (r=-0.844, p<0.001). A cutoff value of eight in ASQoL showed good discriminative properties for impaired QoL where sensitivity and specificity were simultaneously maximized according to disease activity (AUC=0.84 [95% confidence interval (CI): 0.770-0.908, p<0.001]) and the patients’ global health status (AUC=0.85 [95% CI: 0.782-0.923, p<0.001]) in patients with AS. Conclusion: There was a strong correlation between ASQoL and disease activity as well as the patients’ global health status in patients with AS. A cutoff value of eight in ASQoL could be used with good discriminative properties for impaired QoL in AS.